Laser-Assisted Drug Delivery. Issue 8 (August 2016) - Zaleski-Larsen, Lisa Ann; Fabi, Sabrina G.
Abstract : BACKGROUND: Laser-assisted drug delivery (LADD) is an evolving new therapy with many possible applications as a highly targeted customizable method for distribution of drugs within the skin. LADD offers the advantages of accessibility, noninvasiveness, compliance, safety, and effectiveness. OBJECTIVE: To review the available literature regarding LADD. METHODS: A MEDLINE search was performed on LADD from 1989 to 2015, and the results are summarized. Practical applications of these procedures are also discussed. RESULTS: Reports of the use of ablative, nonablative, and fractional lasers as a means to increase cutaneous permeation of the topical application of medications and cosmeceuticals were found. The focus of the review was to demonstrate the variety of topical treatments that have been used with the LADD method and the multitude of future studies needed to fully characterize the best application of this evolving technology. CONCLUSION: The most comprehensive review in the literature to date on LADD is provided. Further studies are needed to fully evaluate the safety, dosing, side effects, and results.